2019
DOI: 10.1098/rsta.2018.0209
|View full text |Cite
|
Sign up to set email alerts
|

On the theory of the unsteady-state growth of spherical crystals in metastable liquids

Abstract: Cite this article: Alexandrov DV, Alexandrova IV. 2019 On the theory of the unsteady-state growth of spherical crystals in metastable liquids. Phil. Trans. R. Soc. A 377: 20180209. http://dx.One contribution of 17 to a theme issue 'Heterogeneous materials: metastable and non-ergodic internal structures' .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…Another significant effect of non-stationary temperature field (normal∂T/normal∂t0) in the absence of attachment kinetics (μkfalse→normal∞) and Gibbs–Thomson effect (χ=0) was considered in recently published papers [38,39]. In these works, based on the methods of differential series and the Laplace–Carson integral transform, it was shown that the radius of a crystal and its growth rate represent the following functions of the melt supercooling normalΔT and time t Rfalse(tfalse)=βtnormalΔT(1β2qTtΔT2)2emand2emdRdt=βnormalΔTfalse(1β2qTtnormalΔTfalse).} Eliminating t from these expressions, we represent dR/dt as a function of Δ T and R of the form (see also [40]) dRdt=βnormalΔT1…”
Section: Transient Dynamics Of Individual Crystals In a Metastable Liquid: The Gibbs–thomson And Atomic Kinetics Effectsmentioning
confidence: 99%
“…Another significant effect of non-stationary temperature field (normal∂T/normal∂t0) in the absence of attachment kinetics (μkfalse→normal∞) and Gibbs–Thomson effect (χ=0) was considered in recently published papers [38,39]. In these works, based on the methods of differential series and the Laplace–Carson integral transform, it was shown that the radius of a crystal and its growth rate represent the following functions of the melt supercooling normalΔT and time t Rfalse(tfalse)=βtnormalΔT(1β2qTtΔT2)2emand2emdRdt=βnormalΔTfalse(1β2qTtnormalΔTfalse).} Eliminating t from these expressions, we represent dR/dt as a function of Δ T and R of the form (see also [40]) dRdt=βnormalΔT1…”
Section: Transient Dynamics Of Individual Crystals In a Metastable Liquid: The Gibbs–thomson And Atomic Kinetics Effectsmentioning
confidence: 99%
“…To answer this question, we solve the corresponding boundary-value problem using the coordinate system of a prolate ellipsoid of revolution. In the limiting case, this theory transforms into the previously developed expressions for spherical crystals [34][35][36]. Using this growth law, we develop in §3 the nucleation theory without fluctuations in particle growth rates.…”
Section: Introductionmentioning
confidence: 99%
“…This paper, which is directly connected with experiments and simulations presented in papers [11,12], opens a new perspective on the theory of phase transformations at the intermediate stage, which is presented in the next paper by Eugenya Makoveeva & Dmitri Alexandrov [15]. In this paper, a new theory describing the evolution of a phase transformation process in supersaturated and supercooled liquids is considered with allowance for the fluctuation corrections in particle's growth rates [14]. Note that some important applications of this theory in the life sciences and biophysics are considered in the last subsection of this issue.…”
Section: (B) Metastable and Non-ergodic Systems Governed By Macroscopmentioning
confidence: 79%
“…Namely, the paper presented by Dmitri Alexandrov & Irina Nizovtseva [18] is devoted to the theoretical development of the nucleation processes and connects the theory and experimental data on protein and insulin crystallization. Specifically, this paper develops the previous papers [14,15] to describe the effect of the 'diffusion' of the particle-size distribution function in the space of particle radii. In addition, the obtained and generalized dynamical laws are used here to describe and explain existing experiments for biomedical applications.…”
Section: (C) Biomedical Applications Of Heterogeneous Materialsmentioning
confidence: 99%